ESTIMASI BIOMASSA POHON MAHONI (Swietenia Macrophylla King) DI AREAL UNSRAT - Martinus Lokbere; Hard N. Pollo; Johny S. Tasirin (COCOS, 2017)
ABSTRACT  Mahogany tree besides capturing carbon for its natural growth, it can be hypotezised that the tree has a capability to reduce CO2, heat energy and other pollutant contents that released to the air.  Total carbon captured by the mahagony tree, then can be estimated quantitavely in form of biomass.  The aims of this research were to calculate biomass content on mahagony trees and to estimate the biomass characters on each part of the trees.  The researh was done in UNSRAT area from June to July 2017 by Cencus Method.  The data were analysed by using Allometric Equations developed to calculate biomass content of mahogany tree.  The result showed that from the 313 trees, the total biomass was 304,052.99 kg.  It was characterized by the biomass content on tree trunks was 5 %, stems 73 %, branches 17 %, branchlets 2 %, and on leaves 3 %. These imply that the mahagony tree can be planted to over released pollutant area in order to reduce the CO2, heat energy and other pollutant contents.  Keywords : Mahogany Tree, carbon, biomass, UNSRAT